A AN ANALYSIS OF DEIXIS IN MOANA (2016) MOVIE: A PRAGMATICS STUDY - Indri Indra Sari; Hanif Nurcholish Adiantika; Eline Rozaliya Winarto (LEAD (Language, Education and Development), 2024)
The research aims to understand the types of deixis in the Moana movie and describe their function in conversation. The study uses qualitative research methods, including reading, watching, listening, and taking notes. The researchers identified three types of deixis: person, spatial, and temporal. Person deixis is ranked first with 92% of the total deixis, followed by spatial deixis at 6% and temporal deixis at 2%. Dexis are found in the introduction, beginning, and end of the story. The deixis function is divided into two: pointing and referring. Pointing is divided into singular and plural forms, providing clarity in communication. Referring is divided into words referring objects, people, and places, working as a link between sentences. The total number of types of deixis in the Moana movie is 1,307.